Peran Dan Strategi Financial Technologi (Fintech)Dalam Upaya Meningkatkan Dana Zakat LAZ Al-Kahfi - Bernad Hananto; Wiranta; Iin Masriah; Suhrowardi; Savero RN (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2024)
Fintech is a new breakthrough in the method of collecting zakat funds, this is not only a method but also one of the strategies to increase zakat fund collection. Fintech makes it easy for muzzaki to pay zakat, compared to paying directly manually at LAZ offices or counters. The type of research used is field research that is. qualitative in which the data is taken directly from the source, using a qualitative descriptive approach, namely research that describes data and information based on facts obtained in the field regarding the implementation of fintech as a strategy to increase zakat fund collection. With the method of interviewing, observation, documentation, and literature and using the SWOT analysis tool. The result of this research is that the Fintech System at LAZ ALKAHFI uses several media in running the fintech system, namely bank transfers via ATM, e-banking and m-banking. besides using websites, applications and social media, as well as collaborating with several e-commerce sites, such as Gojek and Ovo. This system has several weaknesses, one of which is technical problems with virtual numbers and services on the available websites and applications. However, these weaknesses can be minimized by the SWOT method. In the end, the fintech system has a positive effect on increasing the zakat fund at LAZ AL-KAHFI.